PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT TERHADAP PENGEMBANGAN SOCIAL-EMOTIONAL LEARNING - Pakpak Rosadi; Wulandari Putri; Yogi Akin; Didin Budiman (Jurnal Porkes, 2026)
This study was motivated by the importance of developing Social-Emotional Learning (SEL) in elementary school students as an essential 21st-century competency; however, teaching methods that remain teacher-centered lack collaborative interaction, resulting in students’ social-emotional skills not developing optimally. This study aims to determine the effect of the Teams Games Tournament (TGT) learning model, implemented through handball-like games, on the development of SEL in elementary school students. The research method employed an experimental design using a pretest-posttest control group design. The sample consisted of 50 fifth-grade students divided into an experimental group (n = 25) and a control group (n = 25) using cluster random sampling. The instrument used was the Social Emotional Learning Scale (SELS), consisting of 17 items covering three indicators: task articulation, peer relationships, and self-regulation. The results showed a significant increase in the experimental group (sig. < 0.001; Cohen’s d = 1.65), while the control group did not show a significant change (sig. = 0.209). Analysis by indicator showed that task articulation (d = 0.567) and self-regulation (d = 0.489) increased significantly, while peer relationships did not yet show a significant increase (d = 0.327). In conclusion, the TGT learning model using handball-like games has a significant effect on the development of SEL in elementary school students, although the effect varies across indicators.